Leadership theories in management and psychologist educational filed - Hayder Nazar Jawoosh; Abeer Dakhil Hatim; MOHDRADZANI ABDUL RAZAK (physical education and sport sciences college for women/ Baghdad University, 2021)
All domains in this world built based on set of theories. Those theories have been responsible for interpretation of some phenomena and interlocking relationships around us. Commonly, theories are categorized by which aspect is believed. Also,can find a group of theories produced regardingto the leadership domain. This paper will be presented some of these theories like (Great Man Theory, Trait Theory, Behavioral Theories, Contingency Theories, Situational Theory, Transactional Theories, and Transformational Theories). where these theories considered the most popular and common in the field of leader and will be discussed by this work